2020
DOI: 10.1096/fj.201902274r
|View full text |Cite
|
Sign up to set email alerts
|

Induction of activity synchronization among primed hippocampal neurons out of random dynamics is key for trace memory formation and retrieval

Abstract: Memory is thought to be encoded by sparsely distributed neuronal ensembles in memory‐related regions. However, it is unclear how memory‐eligible neurons react during learning to encode trace fear memory and how they retrieve a memory. We implemented a fiber‐optic confocal fluorescence endomicroscope to directly visualize calcium dynamics of hippocampal CA1 neurons in freely behaving mice subjected to trace fear conditioning. Here we report that the overall activity levels of CA1 neurons showed a right‐skewed l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 69 publications
3
28
0
Order By: Relevance
“…According to a recent study, there is a small pool (∼10%) of CA1 pyramidal neurons that are inherently active under resting/ free exploration conditions (named "primed neurons" by the authors), while 70% of pyramidal neurons remain silent regardless of behavioral state, with the rest falling into an intermediate zone between the two extremes (Zhou et al 2020). Trace fear-conditioning did not alter the overall activity architecture of CA1 pyramidal neurons, however, increased coherence and signal-to-noise ratio (SNR) among the primed neurons, without increasing activity of the silent neurons.…”
Section: B a Cmentioning
confidence: 99%
“…According to a recent study, there is a small pool (∼10%) of CA1 pyramidal neurons that are inherently active under resting/ free exploration conditions (named "primed neurons" by the authors), while 70% of pyramidal neurons remain silent regardless of behavioral state, with the rest falling into an intermediate zone between the two extremes (Zhou et al 2020). Trace fear-conditioning did not alter the overall activity architecture of CA1 pyramidal neurons, however, increased coherence and signal-to-noise ratio (SNR) among the primed neurons, without increasing activity of the silent neurons.…”
Section: B a Cmentioning
confidence: 99%
“…5 B,C). Our experiment disinhibited the processed input from MECIII ( Kitamura et al 2014 ), leaving the rest of the HPC processing apparatus largely intact for fine-tuned processing of an artificially boosted temporal signal ( McEchron et al 2003 ; Pastalkova et al 2008 ; MacDonald et al 2011 ; Pelkey et al 2017 ; Marks et al 2019 ; Zhang et al 2019 ; Zhou et al 2020 ). Therefore, this experiment suggests that the Island cells in the MEC exert control over the allowed length of time between events that can become associated across time.…”
Section: Discussionmentioning
confidence: 99%
“…Further, by silencing CA1 engram neurons during memory retrieval, Tanaka and colleagues found compromised reactivation of cortical ensembles (Masamizu et al, 2014 ), confirming a direct link between the CA1 engram and cortical representations. Once an engram has formed, in vivo calcium imaging studies have revealed greater synchrony and higher repetitive activity in engram cells compared to non-engram cells, even in the absence of cue presentation (Ghandour et al, 2019 ; Zhou et al, 2020 ). Together, these data strongly support an indexing function for the hippocampal engram.…”
Section: The Hippocampal Engram and Memorymentioning
confidence: 99%